DIRECTIONS AND WAYS OF ENSURING CONTINUITY IN TEACHING THE NATIVE LANGUAGE OF PRESCHOOLS AND JUNIOR SCHOOLCHILDREN (Pedagogy of Higher and Secondary Education, 2009)
In clause (article) pressing questions of training to the native language of the senior preschool children and pupils of younger school are considered . Ways of maintenance of perspectivity to training are offered to language of children of these age categories.